MOUVEMENT PEDESTRE ET MODALITES SENSORIELLES AU CENTRE VILLE DE SETIF - RAHMANI, A.; NACEUR, F. (Courrier du Savoir, 2014)
This paper tempts to study the way in which pedestrians use, practice and perceive the streets of Setif downtown, a middle city in east of Algeria.     Which are the most repulsive, attractive sections in the pedestrian's course? How are the most used streets perceived and felt by pedestrians?   To  answer  these  questions,  several  streets  characterized  by  varied  pedestrian  fluxes  were  compared.  The  objective  is  to evaluate the impact of their landscape components and sensory modes on the pedestrian choices.     The  research  findings  showed  the  impact of  the  two  landscape components of Setif downtown: Variety and polyvalence on pedestrian attractiveness. In addition, Sensory perception analysis showed that passerby can feel several sensations and behave of several manners in the streets. The street’s ambiance is distinguished by a sensitive dominant phenomenon which in turn influences the quality of the pedestrian’s movements.